Effects of deadlift vs. back squat as post-activation performance enhancement protocols on vertical jump performance of competitive male basketball players - Chen, L.; Lim, J.; Thapa, R. K.; Heng, S. M. K. (Journal of Science in Sport and Exercise, 2025)
Theoretically, post-activation performance enhancement (PAPE) promotes force production and power following heavy resistance training exercises. Resistance training exercises seek to elicit increased force production by preconditioning the muscles during subsequent exercises, such as jumping, throwing, sprinting, and weightlifting. This study aimed to investigate the PAPE effect between barbell back squats (BS) and hexagonal bar deadlifts (HBD) on countermovement jump (CMJ) performance among collegiate basketball players. Eighteen male (with a relative BS one repetition maximum (1RM) of 1.62±0.24 and a relative HBM 1RM of 1.86±0.25) participants were included, who completed a set of 3RM of both exercises in a randomized counterbalanced order before performing a series of CMJs on a force platform at 15 s, 4 min, 8 min, 12 min, 16 min and 20 min post-exercise. A two-way ANOVA with a 7×2 design (time×conditioning activity) was conducted to assess variations between both conditioning activities (CAs) for each dependent variable. No significant differences (all P>0.05) were found between the baseline and the six different jumps, regarding jump height (Eta2p = 0.035), reactive strength index-modified (Eta2p= 0.026), and peak power output (Eta2p= 0.036) across both exercises. However, there was a moderate positive correlation (P=0.008, r=0.604) between relative BS strength and average CMJ height, P but no significant correlation (P>0.05) was found between relative HBD strength and average CMJ height. Despite previous studies reporting the occurrence of PAPE using a similar 3RM load, this study concludes that careful manipulation of PAPE variables (i.e., training status, intensity, volume, exercise selection, rest intervals, and time of day) is necessary to potentially elicit PAPE to enhance subsequent CMJ performance.